Microwave coated paper and paper container
By using the combination of raw materials such as polylactic acid, degradable toughening resin, modified talc powder, modified chitosan fiber in the coating paper, the problem of poor compatibility of polylactic acid materials is solved, and the mechanical properties and overall performance of the coating layer are significantly improved.
Patent Information
- Application Number
- CN202510029031.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2045-01-08
AI Technical Summary
The compatibility between polylactic acid, polyadipic acid/butylene terephthalate and polyhydroxy fatty acid esters is poor, resulting in phase separation of materials during mixing, forming uneven dispersed phases, reducing the overall strength of mechanical properties such as stretching and tearing of materials.
100-110 parts of polylactic acid, 50-60 parts of degradable toughening resin, 20-25 parts of modified talc powder, 15-18 parts of modified chitosan fiber, 3-5 parts of maleic anhydride grafted polypropylene, 1-2 parts of antioxidant, 2-3 parts of anti-ultraviolet agent, and 4-5 parts of pentaerythritol stearate. Through the combination of these raw materials, a uniform coating layer is formed to improve the compatibility and mechanical properties of polylactic acid.
By improving the compatibility of polylactic acid, a uniform coating layer is formed, which significantly improves the toughness, tear resistance and impact resistance of the coating layer, and enhances the overall performance of the packaging material, including gas barrier properties, mechanical properties, moisture-proof and water-proof properties, and heat sealing properties.
Smart Images

Figure BDA0005233621490000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of laminated paper, and in particular to a microwaveable laminated paper and a paper container. Background Art
[0002] Laminated paper is a composite material formed by coating plastic particles (such as polyethylene PE particles) on the surface of paper through a cast film machine. Its manufacturing process mainly includes preparing base paper, coating process, drying treatment, and winding or cutting. Laminated paper is widely used in food, medicine, chemical industry and other fields.
[0003] Microwaveable coated paper is a special coated paper that can be used safely in microwave ovens and will not produce harmful substances or cause fire due to high temperature. Commonly used raw materials for microwaveable coated paper include polylactic acid, polybutylene adipate / terephthalate, and polyhydroxyalkanoate. These materials have excellent heat resistance and biodegradability.
[0004] However, the poor compatibility between polylactic acid, polybutylene adipate / terephthalate, and polyhydroxyalkanoates will cause phase separation of the materials during the mixing process, forming an uneven dispersed phase and reducing the overall strength of the mechanical properties such as tensile and tearing of the materials. Summary of the invention
[0005] In order to improve the problem of poor mechanical properties of coated paper prepared from polylactic acid, the present application provides a microwaveable coated paper and a paper container.
[0006] The present application provides a microwaveable coated paper, which adopts the following technical solution: A microwaveable coated paper comprises paper and a coated layer, wherein the coated layer comprises the following raw materials in parts by weight: 100-110 parts of polylactic acid, 50-60 parts of degradable toughening resin, 20-25 parts of modified talcum powder, 15-18 parts of modified chitosan fiber, 3-5 parts of maleic anhydride grafted polypropylene, 1-2 parts of antioxidant, 2-3 parts of anti-ultraviolet agent and 4-5 parts of pentaerythritol stearate.
[0007] By adopting the above technical solution, polylactic acid has good compatibility and can be well combined with paper to form a uniform coating layer. The polylactic acid coating layer has good high and low temperature resistance, strength and heat sealing properties, and can withstand the temperature changes of hot and cold liquids without leakage or deformation. The addition of degradable toughening resin can significantly improve the toughness of the coating layer, making it more tear-resistant and impact-resistant, thereby improving the overall performance of the packaging material; combined with polylactic acid, it improves the gas barrier, mechanical properties, moisture barrier and water-proof properties, and heat sealing properties of the coating layer. Modified talcum powder has a flaky structure and can form a layered dispersion in the coating layer, providing excellent mechanical performance support for the coating layer, significantly improving the barrier properties of the coated base paper, and improving the thermal stability of the coating layer, so that it can still maintain good performance in a high temperature environment.
[0008] Modified chitosan fiber has excellent antibacterial properties, high strength and toughness, can be closely combined with plastic substrates to form a stable structure, improve the tensile strength, tear strength and puncture resistance of the product, and can significantly improve the mechanical properties of the coating layer. Modified talcum powder is mixed with modified chitosan fiber, and the modified talcum powder can be loaded on the surface of the modified chitosan fiber to improve the density of the raw materials and the mechanical properties of the coating layer; maleic anhydride grafted polypropylene has good compatibility, improves the heat resistance, weather resistance, tensile and impact strength of the coating layer, significantly improves the bonding force between the coating layer and the paper, ensures the close bonding between the coating layer and the substrate, and thus improves the overall strength and durability of the product.
[0009] Antioxidants can protect the material properties of the coating layer, prevent it from deteriorating due to oxidation, delay the oxidation reaction, significantly extend its service life, and improve its weather resistance and stability. Anti-ultraviolet agents can absorb ultraviolet energy and convert it into heat or other harmless forms to release it, thereby avoiding direct damage to the coating layer material by ultraviolet rays, maintaining its original physical and chemical properties, and extending its service life. Pentaerythritol stearate has good lubricity and demoulding properties, which enables it to significantly reduce the friction and adhesion between materials in the coating layer. During the coating process, it can promote the flow of plastics and reduce the adhesion between the mold and the material, thereby improving production efficiency and product quality.
[0010] Preferably, the preparation method of the modified talc powder comprises the following steps: (1) dispersing talc in a dilute nitric acid solution, stirring at room temperature for 30-40 minutes, washing with water, and then dispersing in ethanol, adding a titanate coupling agent, stirring at a temperature of 60-65° C. for 1-2 hours, filtering, and drying to obtain pretreated talc; (2) Dispersing the modified corn stalks in deionized water, adding the pretreated talcum powder and nano-silicon dioxide in step (1), stirring at a temperature of 80-85° C. for 2-3 hours, drying, and grinding to obtain modified talcum powder.
[0011] By adopting the above technical scheme, talcum powder is treated with a dilute nitric acid solution, the dilute nitric acid dissolves or reacts some unnecessary substances, removes impurities on the surface of the talcum powder, the talcum powder is dispersed in ethanol, and a titanate coupling agent is added. The titanate coupling agent reacts with functional groups such as hydroxyl groups on the surface of the talcum powder to form chemical bonds, thereby improving the compatibility and dispersibility of the talcum powder with organic matter; after the treatment with the titanate coupling agent, new functional groups are introduced on the surface of the talcum powder, thereby improving its compatibility and dispersibility with organic matter.
[0012] Modified corn stalks are dispersed in deionized water. Modified corn stalks have good compatibility, air permeability, strength and toughness. Pretreated talcum powder has a flaky structure and can form an effective barrier layer, improve the barrier performance of the coating layer to gas, moisture, etc., and extend the freshness and shelf life of the items in the package; the addition of pretreated talcum powder can enhance the tensile strength, tear strength and other mechanical properties of the coating layer, making the coating layer less likely to be damaged when subjected to external forces, thereby improving the durability of the packaging. Nano-silicon dioxide has an extremely high specific surface area and activity, and can form a close bond with other components in the coating layer, thereby improving the overall strength and toughness of the coating layer, so that the coating layer can better resist deformation and damage when subjected to external forces. Nano-silicon dioxide has excellent dispersibility and stability, and can be evenly distributed in the coating layer to avoid agglomeration and sedimentation.
[0013] Nano-silicon dioxide can be loaded into the structure of talcum powder, and modified corn straw can be tightly combined with nano-silicon dioxide and talcum powder to improve the mechanical properties, wear resistance and barrier properties of the modified talcum powder. It can be subsequently applied to the coating layer to improve the overall strength and toughness, wear resistance and aging resistance of the coating layer, extend the service life of the coating layer, and reduce packaging damage caused by wear and aging.
[0014] Preferably, the mass ratio of the talcum powder, modified corn straw and nano-silicon dioxide is 1:0.4-0.6:0.1-0.2.
[0015] By adopting the above technical solution, the mass ratio of talcum powder, modified corn straw and nano-silicon dioxide is further limited within a certain range, and the comprehensive properties of talcum powder such as mechanical properties, wear resistance and barrier properties are improved. Talc powder has a flaky structure, which can enhance the tensile strength and tear strength of the coating layer; nano-silicon dioxide has an extremely high specific surface area and activity, and can form a close bond with other components in the coating layer, further improving the overall strength and toughness; modified corn straw has cellulose and other components that also help to enhance the physical properties of the coating layer. Modified corn straw can be closely combined with nano-silicon dioxide and talcum powder to improve the comprehensive properties of modified talcum powder, and subsequently applied to the coating layer to improve the wear resistance and aging resistance of the coating layer. Both talcum powder and nano-silicon dioxide can form an effective barrier layer in the coating layer to improve its barrier properties to gas, moisture, etc.
[0016] Preferably, the preparation method of the modified corn stalks comprises the following steps: crushing, drying, and sieving the corn stalks, dispersing them in a sodium hydroxide solution, stirring them at a temperature of 70-75°C for 40-45 minutes, washing them with water, and then dispersing them in deionized water, adding sodium alginate, nanosilver, and xanthan gum, stirring them at a temperature of 80-85°C for 2-3 hours, drying, and grinding to obtain modified corn stalks.
[0017] By adopting the above technical scheme, the corn stalks are crushed and treated with sodium hydroxide solution to destroy the lignin and hemicellulose structure in the corn stalks, making it easier to be combined with other components in the subsequent steps; the corn stalks are washed with water to remove the residual sodium hydroxide and other impurities. The washed corn stalks are dispersed in deionized water again, and sodium alginate, nanosilver and xanthan gum are added. Sodium alginate has good viscosity, film-forming property and biocompatibility, and can be combined with cellulose in the corn stalks to form a complementary fiber network structure, thereby improving the strength and toughness of the system. Nanosilver has antibacterial properties and can be embedded in the network structure formed by sodium alginate and cellulose to increase the antibacterial property of the system. Xanthan gum is a good thickener and can significantly increase the viscosity and stability of the mixture. Sodium alginate, xanthan gum and cellulose are mixed to undergo cross-linking to form a more stable and uniform structure, while increasing the viscosity and mechanical properties of the system.
[0018] Modified corn straw is applied to modified talcum powder, so that the talcum powder and nano-silicon dioxide are tightly bonded. Nano-silicon dioxide is tightly bonded to the structure of the talcum powder through the modified corn straw, thereby improving the mechanical strength and performance stability of the modified talcum powder. It is subsequently applied to the coating layer to improve the corresponding performance of the coating layer.
[0019] Preferably, the method for preparing the modified chitosan fiber comprises the following steps: (1) dispersing chitosan fibers in a sodium hydroxide solution, stirring at 50-55° C. for 1-2 hours, washing, and drying to obtain pretreated chitosan fibers; (2) Dispersing the modified starch in deionized water, adding the pretreated chitosan fiber of step (1), sodium hydroxymethyl cellulose and acetic acid, stirring at a temperature of 70-75° C. for 1-2 h, and drying to obtain modified chitosan fiber.
[0020] By adopting the above technical scheme, the chitosan fiber is first pretreated and treated with a sodium hydroxide solution. The reaction between the chitosan fiber and the sodium hydroxide solution removes the acetyl group in the chitosan molecule, thereby improving the ductility and solubility of the fiber; the purpose of washing is to remove the sodium hydroxide and other impurities remaining on the fiber surface to ensure the purity of the fiber and the safety of subsequent use.
[0021] Modified starch is dispersed in deionized water to form a uniform suspension, and chitosan fiber, sodium hydroxymethyl cellulose, and acetic acid are added. Chitosan fiber has good mechanical properties, antibacterial properties, and biocompatibility. Modified starch can coat chitosan fiber to improve the viscosity and mechanical properties of chitosan fiber. The hydroxyl group of modified starch can hydrogen bond or cross-link with the amino group of chitosan fiber or the hydroxyl group of sodium hydroxymethyl cellulose. Acetic acid adjusts the pH value of the system and plays a catalytic role to promote these reactions. The addition of sodium hydroxymethyl cellulose may also improve the dispersion of fibers and enhance the interaction between fibers, thereby improving the mechanical properties and stability of the composite material.
[0022] When subsequently applied to the coating layer, starch can form a colloidal solution, increase the viscosity of the system, and prevent the liquid components from being lost too quickly, thereby improving the stability and durability of the coating layer. Sodium hydroxymethyl cellulose achieves the purpose of thickening by increasing the viscosity of the solution, thereby improving the texture and stability of the coating layer. In addition, sodium hydroxymethyl cellulose also has good film-forming properties and can form a protective film on the surface of the coating layer to prevent the external environment from damaging the coating layer. Chitosan fiber has a wide antibacterial spectrum and high-efficiency antibacterial activity, which can significantly improve the antibacterial properties of the coating layer, prevent the growth and reproduction of microorganisms, and thus extend the service life of the coating layer.
[0023] Preferably, the mass ratio of the chitosan fiber, the modified starch and the sodium hydroxymethyl cellulose is 1:0.3-0.5:0.08-0.09.
[0024] By adopting the above technical scheme, the mass ratio of chitosan fiber, modified starch and sodium hydroxymethyl cellulose is further limited within a certain range, and the obtained chitosan fiber has excellent mechanical properties and antibacterial properties. The modified starch can coat the chitosan fiber to improve the mechanical properties and viscosity of the chitosan fiber. The sodium hydroxymethyl cellulose makes the chitosan fiber and the modified starch further bonded, thereby improving the comprehensive performance of the system.
[0025] Chitosan fiber has excellent mechanical properties and biocompatibility. The hydroxyl groups of modified starch can form hydrogen bonds or cross-linking reactions with the amino groups of chitosan fiber or the hydroxyl groups of sodium hydroxymethylcellulose, thus enhancing the strength and toughness of the coating layer, and improving the water resistance and weather resistance of the coating layer. As a thickener and stabilizer, sodium hydroxymethylcellulose can increase the cohesion of the coating layer, making it tighter and tougher. The thickening effect of sodium hydroxymethylcellulose can improve the coating and uniformity of the coating layer, making it easier to process and apply.
[0026] Preferably, the preparation method of the modified starch comprises the following steps: dispersing glutinous rice starch in a sodium hydroxide solution, stirring at 60-65° C. for 1-2 hours, centrifuging the starch milk, pouring off the supernatant, adding water and shaking, and then centrifuging, repeating the operation until the starch milk becomes neutral, filtering the starch milk and drying it to obtain pretreated starch, and then dispersing the starch in deionized water, adding calcium carbonate and montmorillonite, stirring at 80-85° C. for 2-3 hours, drying, and grinding to obtain modified starch.
[0027] By adopting the above technical scheme, glutinous rice starch is dispersed in a sodium hydroxide solution, causing the internal breakage of the starch molecules and the formation of a cross-linked structure, so that the starch molecules are transformed from a granular structure to a uniform colloidal structure. Centrifugation can remove excess water and unreacted sodium hydroxide in the starch milk, and the obtained pretreated starch has improved starch viscosity and uniformity.
[0028] Starch is dispersed in water to form a starch emulsion. Calcium carbonate has high hardness and stability and can be embedded in the starch structure to increase the hardness and density of the entire system. The surface of montmorillonite has a large number of hydroxyl groups and negative charges, which can adsorb cations and organic molecules in water and promote the dispersion of calcium carbonate and starch, helping to enhance the uniformity and stability of the mixture.
[0029] The hydroxyl groups on the starch molecular chain can interact with the calcium ions on the surface of calcium carbonate or the hydroxyl groups on the surface of montmorillonite to form a cross-linked structure, which helps to improve the stability and mechanical strength of the mixture. Calcium carbonate particles will be wrapped by starch colloids in the mixed system to form a starch-calcium carbonate complex. This complex helps to prevent the agglomeration and sedimentation of calcium carbonate particles and improve the uniformity of the mixture. Starch, calcium carbonate and montmorillonite can form a synergistic enhancement effect in the mixture, and the interaction between them can enhance the mechanical strength, heat resistance and stability of the entire system. It is subsequently applied to the coating layer to enhance the adhesion between the coating layer and the substrate, and improve the mechanical properties, wear resistance, barrier and heat resistance of the coating layer.
[0030] Preferably, the degradable toughening resin is selected from at least one of polyhydroxyalkanoates, polybutylene succinate, polybutylene adipate terephthalate, and polyhydroxybutyrate.
[0031] By adopting the above technical solution, the toughness of the degradable toughening resin reinforced material can be effectively improved to improve the impact strength and tear strength of the coating layer, making it more durable and less prone to damage when facing external forces.
[0032] In a second aspect, the present application also provides a method for preparing microwaveable coated paper, comprising the following steps: Mixing polylactic acid, degradable toughening resin, modified talcum powder, modified chitosan fiber, maleic anhydride grafted polypropylene, antioxidant, anti-ultraviolet agent, and pentaerythritol stearate to obtain a premixed raw material; Extruding and granulating the premixed raw materials to obtain a composite modified masterbatch; The composite modified masterbatch is dried and then cast coated with paper to obtain microwaveable coated paper.
[0033] By adopting the above technical scheme and the above preparation method, the process time is short and the operation is simple, which helps to improve the production efficiency of coated paper. The obtained microwave coated paper has comprehensive properties such as good mechanical properties and stability.
[0034] In a third aspect, the present application further provides a paper container, including a container body, wherein the inner and outer walls of the container body are bonded with the above-prepared coated paper, and the adhesive used for bonding is acrylic resin.
[0035] In summary, this application has the following beneficial effects: 1. In this application, polylactic acid has good compatibility and can be well combined with paper to form a uniform coating layer. The polylactic acid coating layer has good high and low temperature resistance, strength and heat sealing properties, and can withstand temperature changes of cold and hot liquids without leakage or deformation.
[0036] 2. The modified talcum powder in this application has a flaky structure and can form a layered dispersion in the coating layer, providing excellent mechanical performance support for the coating layer, thereby significantly improving the barrier properties of the coated base paper and improving the thermal stability of the coating layer, so that it can still maintain good performance in a high temperature environment.
[0037] 3. The modified chitosan fiber in this application has excellent antibacterial properties, high strength and toughness, can be tightly combined with the plastic substrate to form a stable structure, improve the tensile strength, tear strength and puncture resistance of the product, and can significantly improve the mechanical properties of the coating layer. DETAILED DESCRIPTION
[0038] The present application is further described in detail below with reference to the embodiments.
[0039] The raw materials used in the examples and comparative examples can all be obtained commercially.
[0040] Preparation example of modified talc Preparation Example 1-1 The preparation method of modified talcum powder comprises the following steps: (1) 50 kg of talc powder was dispersed in 70 L of a 20% by mass dilute nitric acid solution, stirred at room temperature for 35 min, washed with water, and then dispersed in 80 L of ethanol, titanate coupling agent HY401 was added, stirred at 65 ° C for 2 h, filtered, and dried to obtain pretreated talc powder; (2) Dispersing the modified corn straw in 80 L of deionized water, adding the pretreated talcum powder and nano-silicon dioxide in step (1), stirring at a temperature of 85° C. for 3 h, drying, and grinding to obtain modified talcum powder.
[0041] The mass ratio of talcum powder, modified corn straw and nano-silicon dioxide is 1:0.4:0.2.
[0042] The preparation method of modified corn stalks comprises the following steps: crushing and drying 100 kg of corn stalks, passing through a 60-mesh sieve, dispersing the corn stalks in 120 L of a sodium hydroxide solution with a mass fraction of 10%, stirring the solution at a temperature of 75 DEG C for 45 minutes, washing the solution with water, dispersing the solution in 150 L of deionized water, adding 25 kg of sodium alginate, 30 kg of nano silver and 20 kg of xanthan gum, stirring the solution at a temperature of 85 DEG C for 3 hours, drying and grinding the solution to obtain the modified corn stalks.
[0043] Preparation Example 1-2 The difference from Preparation Example 1-1 is that in step (2), no modified corn stalks are added.
[0044] Preparation Example 1-3 The difference from Preparation Example 1-1 is that in step (2), no nano-silicon dioxide is added.
[0045] Preparation Example 1-4 The difference from Preparation Example 1-1 is that the mass ratio of talcum powder, modified corn straw and nano-silicon dioxide is 1:0.6:0.1.
[0046] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of talcum powder, modified corn straw and nano-silicon dioxide is 1:0.1:0.7.
[0047] Preparation Example 1-6 The difference from Preparation Example 1-1 is that sodium alginate is not added in the preparation method of the modified corn stalk.
[0048] Preparation Example 1-7 The difference from Preparation Example 1-1 is that in the preparation method of the modified corn stalk, no nanosilver is added.
[0049] Preparation Example 1-8 The difference from Preparation Example 1-1 is that no xanthan gum is added in the preparation method of the modified corn straw.
[0050] Preparation example of modified chitosan fiber Preparation Example 2-1 The preparation method of modified chitosan fiber comprises the following steps: (1) dispersing 30 kg of chitosan fibers in 50 L of a 0.8 mol / L sodium hydroxide solution, stirring at 55° C. for 2 h, washing, and drying to obtain pretreated chitosan fibers; (2) Dispersing the modified starch in 90 L of deionized water, adding the pretreated chitosan fiber of step (1), sodium hydroxymethyl cellulose, and 10 L of acetic acid, stirring at 75° C. for 2 h, and drying to obtain modified chitosan fiber.
[0051] The mass ratio of chitosan fiber, modified starch and sodium hydroxymethyl cellulose is 1:0.3:0.09.
[0052] The preparation method of modified starch comprises the following steps: dispersing 30 kg of glutinous rice starch in 50 L of 0.05% sodium hydroxide solution, stirring at 65 DEG C for 2 hours, centrifuging the starch milk, pouring out the supernatant, adding water and shaking, and then centrifuging, repeating the operation until the starch milk becomes neutral, filtering the starch milk and drying it to obtain pretreated starch, and then dispersing the pretreated starch in 90 L of deionized water, adding 10 kg of calcium carbonate and 15 kg of montmorillonite, stirring at 85 DEG C for 3 hours, drying, and grinding to obtain modified starch.
[0053] Preparation Example 2-2 The difference from Preparation Example 2-1 is that in step (2), no modified starch is added.
[0054] Preparation Example 2-3 The difference from Preparation Example 2-1 is that in step (2), sodium hydroxymethyl cellulose is not added.
[0055] Preparation Example 2-4 The difference from Preparation Example 2-1 is that the mass ratio of chitosan fiber, modified starch and sodium hydroxymethyl cellulose is 1:0.5:0.08.
[0056] Preparation Example 2-5 The difference from Preparation Example 2-1 is that the mass ratio of chitosan fiber, modified starch and sodium hydroxymethyl cellulose is 1:0.1:0.2.
[0057] Preparation Example 2-6 The difference from Preparation Example 2-1 is that calcium carbonate is not added in the preparation method of the modified starch.
[0058] Preparation Example 2-7 The difference from Preparation Example 2-1 is that no montmorillonite is added in the preparation method of the modified starch. Example
[0059] Example 1 A microwaveable coated paper comprises paper and a coated layer, wherein the coated layer comprises the following raw materials by weight: 100 kg of polylactic acid, 50 kg of degradable toughening resin, 20 kg of modified talcum powder, 15 kg of modified chitosan fiber, 3 kg of maleic anhydride grafted polypropylene, 1 kg of antioxidant, 2 kg of anti-ultraviolet agent and 5 kg of pentaerythritol stearate.
[0060] The degradable toughening resin is polyhydroxyalkanoate, the antioxidant is antioxidant 1010, and the anti-ultraviolet agent is UV-360, which are purchased from Nanjing Milan Chemical Co., Ltd.
[0061] The method for preparing microwaveable coated paper comprises the following steps: putting polylactic acid, degradable toughening resin, modified talcum powder, modified chitosan fiber, maleic anhydride grafted polypropylene, antioxidant, anti-ultraviolet agent and pentaerythritol stearate into a dry mixer and mixing to obtain a premixed raw material; The premixed raw materials are put into a twin-screw extruder for extrusion granulation to obtain a composite modified masterbatch; The composite modified masterbatch is dried and then cast coated with paper to obtain microwaveable coated paper.
[0062] When the premixed raw materials are fed into a twin-screw extruder for extrusion granulation, the temperatures in the mixing zone are set to 120°C, 170°C, 200°C, 200°C, 180°C, and 170°C in sequence; the temperature of the cast coating is 180°C, and the thickness of the coating layer is 10 μm.
[0063] The modified talc powder was prepared by using Preparation Example 1-1; and the modified chitosan fiber was prepared by using Preparation Example 2-1.
[0064] Example 2 A microwaveable coated paper, which differs from Example 1 in that the coating layer comprises the following raw materials by weight: 110 kg of polylactic acid, 60 kg of degradable toughening resin, 25 kg of modified talcum powder, 18 kg of modified chitosan fiber, 5 kg of maleic anhydride grafted polypropylene, 2 kg of antioxidant, 3 kg of anti-ultraviolet agent, and 4 kg of pentaerythritol stearate.
[0065] Example 3 A microwaveable coated paper, which is different from Example 1 in that the modified talcum powder is prepared using Preparation Example 1-2.
[0066] Example 4 A microwaveable coated paper, which is different from Example 1 in that the modified talcum powder is prepared using Preparation Examples 1-3.
[0067] Example 5 A microwaveable coated paper, which is different from Example 1 in that the modified talcum powder is prepared using Preparation Examples 1-4.
[0068] Example 6 A microwaveable coated paper, which is different from Example 1 in that the modified talcum powder is prepared using Preparation Examples 1-5.
[0069] Example 7 A microwaveable coated paper, which is different from Example 1 in that the modified talcum powder is prepared using Preparation Examples 1-6.
[0070] Example 8 A microwaveable coated paper, which is different from Example 1 in that the modified talcum powder is prepared using Preparation Examples 1-7.
[0071] Example 9 A microwaveable coated paper, which is different from Example 1 in that the modified talcum powder is prepared using Preparation Examples 1-8.
[0072] Example 10 A microwaveable coated paper, which is different from Example 1 in that the modified chitosan fiber is prepared using Preparation Example 2-2.
[0073] Embodiment 11 A microwaveable coated paper, which is different from Example 1 in that the modified chitosan fiber is prepared using Preparation Example 2-3.
[0074] Example 12 A microwaveable coated paper, which is different from Example 1 in that the modified chitosan fiber is prepared using Preparation Examples 2-4.
[0075] Embodiment 13 A microwaveable coated paper, which is different from Example 1 in that the modified chitosan fiber is prepared using Preparation Examples 2-5.
[0076] Embodiment 14 A microwaveable coated paper, which is different from Example 1 in that the modified chitosan fiber is prepared using Preparation Examples 2-6.
[0077] Embodiment 15 A microwaveable coated paper, which is different from Example 1 in that the modified chitosan fiber is prepared using Preparation Examples 2-7.
[0078] Comparative Example Comparative Example 1 A microwaveable coated paper, which differs from Example 1 in that modified talcum powder is not added.
[0079] Comparative Example 2 A microwaveable coated paper, which is different from Example 1 in that the modified talcum powder is replaced by an equal amount of talcum powder.
[0080] Comparative Example 3 A microwaveable coated paper, which differs from Example 1 in that modified chitosan fiber is not added.
[0081] Comparative Example 4 A microwaveable coated paper, which differs from Example 1 in that the modified chitosan fiber is replaced by an equal amount of chitosan fiber.
[0082] Performance testing The performance of the microwaveable coated paper prepared in Examples 1-15 and Comparative Examples 1-4 was tested: The tensile strength refers to GB / T 12914-2018 "Paper and paperboard - Determination of tensile strength - Constant rate tensile method (20mm / min)", the tear resistance refers to GB / T 455-2002 "Paper and paperboard - Determination of tear resistance", the folding endurance refers to GB / T 457-1989 "Determination of folding endurance of paper", and the adhesion refers to GB / T 36392-2018 "Laminated paper and paperboard for food packaging".
[0083] Degradation performance: The samples were landfilled in the soil for degradation tests according to GB / T39951-2021 "Evaluation Method for Degradation Performance of Disposable Paper Products". After a fixed number of days of 45d and 90d, the residual weight was recorded and the weight loss rate was calculated. The test results are shown in Table 1.
[0084] Table 1 Test data of embodiments and comparative examples As can be seen from Table 1, the coated paper prepared in Examples 1-2 of the present application has good mechanical properties, degradation properties and adhesion, wherein the tensile strength of Example 1 is 4.78KN.m, the tear strength is 489mN, the weight loss rates at 45d and 90d are 55.2% and 93.7% respectively, the folding endurance is 151 times, and the adhesion is 35N / inch. This indicates that the prepared coating layer has good tensile strength and tear strength, and the prepared coating layer has good adhesion with the paper, ensuring the close bonding between the coating layer and the substrate, thereby improving the overall strength and durability of the product.
[0085] In the preparation method of modified talc powder in Examples 3-4, modified corn straw and nano-silicon dioxide are not added respectively. In Examples 5-6, the mass ratio of talc powder, modified corn straw and nano-silicon dioxide is changed. It can be seen from Table 1 that the test results of tensile strength, tear strength, weight loss rate at 45d and 90d, folding endurance and adhesion of Examples 3-4 are significantly worse than those of Examples 1-2 and Example 5, while the corresponding performance test of Example 6 is better than that of Examples 3-4, but worse than that of Examples 1-2 and Example 5, indicating that modified corn straw can be closely combined with nano-silicon dioxide and talc powder to improve the comprehensive performance of modified talc powder, and is subsequently applied to the coating layer to improve the wear resistance and aging resistance of the coating layer. Both talc powder and nano-silicon dioxide can form an effective barrier layer in the coating layer to improve the mechanical properties and adhesion of the coating layer.
[0086] In the preparation method of modified corn stalks of Examples 7-9, sodium alginate, nanosilver and xanthan gum are not added respectively. As can be seen from Table 1, the test results of tensile strength, tear strength, weight loss rate at 45d and 90d, folding endurance and adhesion of Examples 7-9 are significantly better than those of Example 3, but worse than those of Examples 1-2 and Example 5, indicating that sodium alginate has good viscosity, film-forming property and biocompatibility, and can combine with cellulose in corn stalks to form a complementary fiber network structure, thereby improving the strength and toughness of the system; nanosilver has antibacterial properties and can be embedded in the network structure formed by sodium alginate and cellulose to increase the antibacterial and mechanical properties of the system; xanthan gum can increase the viscosity and stability of the mixture, while increasing the viscosity and mechanical properties of the system.
[0087] In the preparation method of the modified chitosan fiber of Examples 10-11, modified starch and sodium hydroxymethyl cellulose are not added respectively, and the mass ratio of chitosan fiber, modified starch and sodium hydroxymethyl cellulose is changed in Examples 12-13. It can be seen from Table 1 that the test results of tensile strength, tear strength, weight loss rate at 45d and 90d, folding endurance and adhesion of Examples 10-11 are significantly worse than those of Examples 1-2 and Example 12, while the corresponding performance test of Example 13 is better than that of Examples 10-11, but worse than that of Examples 1-2 and Example 12, indicating that the chitosan fiber has excellent mechanical properties and biocompatibility, and the hydroxyl group of the modified starch can hydrogen bond or cross-link with the amino group of the chitosan fiber or the hydroxyl group of sodium hydroxymethyl cellulose to enhance the strength and toughness of the coating layer, while improving the water resistance, adhesion, weather resistance and mechanical properties of the coating layer.
[0088] In the preparation methods of the modified starches of Examples 14-15, calcium carbonate and montmorillonite are not added respectively. As can be seen from Table 1, the test results of tensile strength, tear strength, weight loss rate at 45d and 90d, folding endurance and adhesion of Examples 14-15 are significantly better than those of Example 10, but worse than those of Examples 1-2 and Example 12, indicating that calcium carbonate has higher hardness and stability, can be embedded in the starch structure, and increase the hardness and density of the entire system; montmorillonite is cross-linked with starch to improve the stability and mechanical strength of the mixture, and is subsequently applied to the coating layer to enhance the adhesion between the coating layer and the substrate, and improve the mechanical properties, wear resistance, barrier properties and heat resistance of the coating layer.
[0089] No modified talcum powder or modified chitosan fiber is added to Comparative Example 1 and Comparative Example 3, respectively. As can be seen from Table 1, the test results of tensile strength, tear strength, weight loss rate at 45d and 90d, folding endurance and adhesion of Comparative Example 1 and Comparative Example 3 are significantly worse than those of Examples 1-2, indicating that modified talcum powder can form a layered dispersion in the coating layer, provide excellent mechanical performance support for the coating layer, improve the stability of the coating layer, and maintain good performance; modified chitosan fiber has excellent antibacterial properties, high strength and toughness, can be tightly combined with the plastic substrate to form a stable structure, improve the tensile strength, tear strength and puncture resistance of the product, and can improve the mechanical properties of the coating layer.
[0090] In Comparative Examples 2 and 4, the modified talc is replaced by an equal amount of talc, and the modified chitosan fiber is replaced by an equal amount of chitosan fiber. As can be seen from Table 1, the test results of tensile strength, tear strength, weight loss rate at 45d and 90d, folding endurance and adhesion of Comparative Examples 2 and 4 are significantly worse than those of Examples 1-2, but better than those of Comparative Examples 1 and 3, indicating that the modified talc and modified chitosan fiber of the present application have good mechanical properties, thereby improving the mechanical properties of the coating layer and maintaining the durability and stability of the coated paper.
[0091] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A microwaveable coated paper, characterized in that: The invention comprises paper and a coating layer, wherein the coating layer comprises the following raw materials in parts by weight: 100-110 parts of polylactic acid, 50-60 parts of degradable toughening resin, 20-25 parts of modified talcum powder, 15-18 parts of modified chitosan fiber, 3-5 parts of maleic anhydride grafted polypropylene, 1-2 parts of antioxidant, 2-3 parts of anti-ultraviolet agent and 4-5 parts of pentaerythritol stearate.
2. The microwaveable coated paper according to claim 1, characterized in that: The preparation method of the modified talcum powder comprises the following steps: (1) Dispersing talc in a dilute nitric acid solution, stirring at room temperature for 30-40 minutes, washing with water, and then dispersing in ethanol, adding a titanate coupling agent, stirring at a temperature of 60-65°C for 1-2 hours, filtering, and drying to obtain pretreated talc; (2) Dispersing the modified corn straw in deionized water, adding the pretreated talcum powder and nano-silicon dioxide in step (1), stirring at a temperature of 80-85° C. for 2-3 h, drying, and grinding to obtain modified talcum powder.
3. The microwaveable coated paper according to claim 2, characterized in that: The mass ratio of the talcum powder, the modified corn straw and the nano silicon dioxide is 1:0.4-0.6:0.1-0.
2.
4. The microwaveable coated paper according to claim 2, characterized in that: The preparation method of the modified corn stalk comprises the following steps: crushing and drying the corn stalk, sieving, dispersing in a sodium hydroxide solution, stirring at a temperature of 70-75°C for 40-45 minutes, washing, dispersing in deionized water, adding sodium alginate, nano silver and xanthan gum, stirring at a temperature of 80-85°C for 2-3 hours, drying, and grinding to obtain the modified corn stalk.
5. The microwaveable coated paper according to claim 1, characterized in that: The preparation method of the modified chitosan fiber comprises the following steps: (1) dispersing chitosan fibers in a sodium hydroxide solution, stirring at 50-55° C. for 1-2 hours, washing, and drying to obtain pretreated chitosan fibers; (2) Dispersing the modified starch in deionized water, adding the pretreated chitosan fiber of step (1), sodium hydroxymethyl cellulose and acetic acid, stirring at a temperature of 70-75° C. for 1-2 hours, and drying to obtain modified chitosan fiber.
6. The microwaveable coated paper according to claim 5, characterized in that: The mass ratio of the chitosan fiber, the modified starch and the sodium hydroxymethyl cellulose is 1:0.3-0.5:0.08-0.
09.
7. The microwaveable coated paper according to claim 5, characterized in that: The preparation method of the modified starch comprises the following steps: dispersing glutinous rice starch in a sodium hydroxide solution, stirring at 60-65°C for 1-2h, centrifuging the starch milk, pouring out the supernatant, adding water and shaking, and then centrifuging, repeating the operation until the starch milk becomes neutral, filtering the starch milk and drying it to obtain pretreated starch, and then dispersing the starch in deionized water, adding calcium carbonate and montmorillonite, stirring at 80-85°C for 2-3h, drying, and grinding to obtain the modified starch.
8. The microwaveable coated paper according to claim 1, characterized in that: The degradable toughening resin is selected from at least one of polyhydroxyalkanoates, polybutylene succinate, polybutylene adipate terephthalate, and polyhydroxybutyrate.
9. The method for preparing a microwaveable coated paper according to claim 1, characterized in that: The steps include: Mixing polylactic acid, degradable toughening resin, modified talcum powder, modified chitosan fiber, maleic anhydride grafted polypropylene, antioxidant, anti-ultraviolet agent, and pentaerythritol stearate to obtain a premixed raw material; Extruding and granulating the premixed raw materials to obtain a composite modified masterbatch; The composite modified masterbatch is dried and then cast coated with paper to obtain microwaveable coated paper.
10. A paper container, comprising a container body, characterized in that: The inner and outer walls of the container body are bonded with the coated paper according to any one of claims 1 to 9, and the adhesive used for bonding is acrylic resin.
Citation Information
Patent Citations
Plant fiber-reinforced polylactic acid foam material and preparation method thereof
CN101955638A
Biodegradable PE-coated paper material and preparation method thereof
CN102558797A
Method for increasing capacity of biodegradable polyester blend film
CN103172988A
Preparation method for two-color oil-proof antibacterial food packaging paper
CN108130818A
Degradable polylactic acid paper cup and preparation method thereof
CN110184851A